О ТВОРЧЕСКОМ ИСПОЛЬЗОВАНИИ ЗАИМСТВОВАННОЙ ЛЕКСИКИ В ОБУЧЕНИИ РУССКОМУ ЯЗЫКУ - Кощанов, К.М. (SCIENCE and SOCIETY, 2019)
In the article there are presented the ways of the successful use of the enormous mass of the borrowed Russian and International lexical units in the practice of effective teaching the Russian language to Karakalpak pupils.